2008
DOI: 10.1291/hypres.31.1093
|View full text |Cite
|
Sign up to set email alerts
|

Leptin-Receptor Polymorphisms Relate to Obesity through Blunted Leptin-Mediated Sympathetic Nerve Activation in a Caucasian Male Population

Abstract: Leptin plays a key role in the regulation of body weight through the sympathetic nervous system; however, the contributions of leptin-receptor polymorphisms to obesity and sympathetic nerve activity have not been fully clarified. In the present study, we examined the relationships between leptin-receptor polymorphisms, plasma leptin and whole-body norepinephrine (NE) spillover as an index of sympathetic nerve activity in a Caucasian male cohort. In 129 young healthy normotensive men with a wide range of body m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
2
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 44 publications
2
32
2
2
Order By: Relevance
“…In a Caucasian male population, carriers of the Asn656-allele had significantly higher levels of plasma leptin ( Table 2) [148]. Another study revealed that in 132 men with obesity undergoing a polyunsaturated fatty acid-enriched hypocaloric diet, leptin levels were significantly decreased in the group homozygote for the Lys656-allele after 2 months of intervention [152].…”
Section: Leptin Receptor (Lepr)mentioning
confidence: 98%
See 1 more Smart Citation
“…In a Caucasian male population, carriers of the Asn656-allele had significantly higher levels of plasma leptin ( Table 2) [148]. Another study revealed that in 132 men with obesity undergoing a polyunsaturated fatty acid-enriched hypocaloric diet, leptin levels were significantly decreased in the group homozygote for the Lys656-allele after 2 months of intervention [152].…”
Section: Leptin Receptor (Lepr)mentioning
confidence: 98%
“…The p.Q223R (rs1137101 A/G) polymorphism in LEPR is the most investigated. While some studies reported an association of the variant coding for the glutamine ("Q") allele with higher plasma leptin serum levels [142,143], others found that the arginine ("R") allele was associated with increased leptin levels ( Table 2) [144][145][146][147][148]. At the amino acid level, this polymorphism leads to a change in electric charge from neutral to positive in this position, and may thereby affect the functionality of the receptor and alter its signaling capacity.…”
Section: Leptin Receptor (Lepr)mentioning
confidence: 99%
“…The p.Q223R (rs1137101 A/G) polymorphism in LEPR is the most investigated. While some studies reported an association of the variant coding for the glutamine ("Q") allele with higher plasma leptin serum levels [142,143], others found that the arginine ("R") allele was associated with increased leptin levels ( Table 2) [144][145][146][147][148]. At the amino acid level, this polymorphism leads to a change in electric charge from neutral to positive in this position, and may thereby affect the functionality of the receptor and alter its signaling capacity.…”
Section: Leptin Receptor (Lepr)mentioning
confidence: 99%
“…The presence of the Q223R LEPR G allele was previously associated with obesity [46][47][48]. However, the findings regarding its association with altered glucose and lipid metabolism are conflicting [48][49][50][51].…”
Section: Prace Oryginalnementioning
confidence: 99%